PORTRAYING HOW EFL TEACHERS APPLIED TRANSLANGUAGING IN THE SPEAKING CLASSROOM - Yustini, Rosa; Nugraha, Irsyad; Fajriah, Yustika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Translanguaging has emerged as a transformative pedagogical orientation in English as a Foreign Language (EFL) classrooms, challenging traditional monolingual norms by utilizing learners' full linguistic repertoires. However, how teachers systematically manage and execute translanguaging strategies during oral speaking activities remains under-explored. This qualitative descriptive study portrays how EFL teachers apply translanguaging strategies to manage classroom interactions and facilitate students' oral English production. Data were gathered through non-participant classroom observations using structured checklists across three senior high school classes and semi-structured in-depth interviews with three English teachers at a multilingual senior high school in West Java, Indonesia. Utilizing thematic analysis, the findings reveal four core instructional translanguaging strategies: (1) instructional scaffolding through linguistic starters and synonym prompting, (2) non-disruptive reformulation and modeling, (3) strategic code-switching for conceptual clarification and instruction, and (4) peer-collaborative translanguaging to mitigate speaking anxiety among low-proficiency learners. Observational evidence confirms that deliberate translanguaging regulation acts as a vital cognitive bridge that enhances student participation without reducing exposure to the target language. The study highlights that managing translanguaging requires a flexible, goal-oriented balance where the first language serves as a temporary scaffolding mechanism while maintaining English as the primary communicative goal.